Research Progress of Biocontrol Bacillus on Postharvest Diseases of Fruits and Vegetables - Man ZOU; Yushi CHEN; Chunyan XU; Xiangzheng YANG; Wenting BAO; Chuanzeng WANG; Peipei ZHU; Yanan MA; Yong ZHANG; Li XIN; Yilun CHEN; Qian ZHANG (Shipin gongye ke-ji, 2023)
During postharvest storage and transportation, fruits and vegetables are prone to decay and deterioration due to the infection of pathogenic bacteria. The control of postharvest diseases mainly relies on chemical synthetic fungicides, but long-term use will lead to environmental pollution and food safety problems. Biological control has the characteristic of green environmental protection and is gradually being applied. Bacillus, as an important biocontrol bacterium, plays an important role in the prevention and control of postharvest diseases of fruits and vegetables. At present, there are a lot of studies on the prevention and control of postharvest diseases of fruits and vegetables by biocontrol Bacillus. In this paper, the species, action mechanism and application status of biocontrol Bacillus in postharvest diseases are reviewed in order to provide reference for the application and development of biocontrol bacillus in postharvest diseases of fruits and vegetables.